2018
DOI: 10.15403/jgld.2014.1121.272.mor
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality of Hepatic Right Lobe Living Donors: Systematic Review and Perspectives

Abstract: Background & Aims: The main restriction in the development of adult-adult Living Donor Liver Transplantation (LDLT) is the risk of morbidity and mortality for donors, which raises ethical questions. The objectives of this study are to review published studies dealing with morbidity and mortality in LDLT and to identify the proposed management and strategies for preventing donor mortality and morbidity in LDLT.Methods: The Medline database was searched from 2000 to 2017 using the MeSH terms “liver transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Recipients of the RPS grafts had the following risks of postoperative complications: overall mortality rate of 14.5%, bile leakage of 8.7%, biliary stenosis of 18.8%, hepatic artery thrombosis of 8.7%, and liver re-transplantation of 2.9%. A recent review regarding RL procurement has reported 23 donor deaths between 1999 and 2017, and high morbidity ranging from 10% to 78.3% [7]. Regarding recipients' outcome, two of the included studies reported outcome in the RPS graft and the RL graft [13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recipients of the RPS grafts had the following risks of postoperative complications: overall mortality rate of 14.5%, bile leakage of 8.7%, biliary stenosis of 18.8%, hepatic artery thrombosis of 8.7%, and liver re-transplantation of 2.9%. A recent review regarding RL procurement has reported 23 donor deaths between 1999 and 2017, and high morbidity ranging from 10% to 78.3% [7]. Regarding recipients' outcome, two of the included studies reported outcome in the RPS graft and the RL graft [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Donation of the right lobe (RL) graft is limited by the minimal liver remnant in order to avoid small-for-size risk for the donor [5,6]. Furthermore, a recent review has shown that morbidity and mortality of RL procurement still remains a concern, leading to a restriction in the development of LDLT [7].…”
Section: Introductionmentioning
confidence: 99%
“…As centers gained more experience, the number of procedures performed in the United States peaked in 2001 at approximately 10% of total adult liver transplants but has since remained 5% (Figure 1, Panel A). A highly publicized live liver donor mortality in 2001 and adoption of the MELD‐based organ allocation in 2002 are factors which may have contributed to the decline in LDLT since the early 2000s in the United States …”
Section: Introductionmentioning
confidence: 99%
“…Even though donor mortality is a rare event (0.5% for right hepatectomy and 0.1-0.3% for left hepatectomy [ 2 3 ], it should be addressed as a catastrophe as it affects the recipient, the families of both the donor and recipient, and all of the clinicians involved in the LDLT process. From 1999 to 2017, 23 deaths worldwide have been reported [ 11 ]. All efforts should be made to minimize the possibility of donor mortality.…”
Section: Discussionmentioning
confidence: 99%